Русские не сдаются: [роман] / Антон Ильин - Ильин Антон (Смерш, 2004)
Экземпляры: аб. (2005) / Инвентарный номер: 49369 / Цена: / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: И 46 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44